Pengaruh Penggunaan Metode Fonik Berbantuan Flash Card Terhadap Perkembangan Bahasa Anak Dan Kemampuan Membaca Awal Anak TK (The Effect of Using Flash Card Assisted Phonics Methods on Children's Language Development and Early Reading Ability in Kindergar - Istiqomah, Ria; Sumiharsono, Rudy; Triwahyuni, Eges (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study was to find out whether using the Flashcard Assisted Phonics Method could improve children's language development and early reading skills. Variable X (Flashcard Assisted Phonics Method) 9 indicators: 1) sound letters, 2) search for sound letters in words, 3) search for sounds in objects, 4) find sounds in cards, 5) feel letters, 6) search for letters in text, 7) looking for letter equivalents, 8) connecting vowel sounds, 9) forming words. Y1 (child language development) 7 indicators: 1) speak fluently, 2) tell stories, 3) name objects, 4) sort the picture series, 5) tell the pictures they made, 6) follow 1-2 commands, 7) make words. Variable Y2 (initial reading ability) 4 indicators: 1) pronunciation and intonation of sentences, 2) letters that are widely used in words, 3) meaningful new words, 4) familiar and new pronunciation, intonation. Research design: causal quantitative, determination of research area: purposive sampling area, determination of respondents: population research area. Data collection: 1). observation, 2). interview, 3). document. Data analysis 1) Instrument test, 2) Classical assumption test, 3) hypothesis test. Results of t-test the effect of Flashcard Assisted Phonics Method on children's language development (11.829> 2.04841), t test of the effect of Flashcard Assisted Phonics Method on early reading ability (6.667> 2.04841), the results of the F test of the effect of the Flashcard Assisted Phonics Method on children's language development and early reading skills together (83.205> 3.34). So it can be concluded that the Flashcard Assisted Phonics Method has an effect on children's language development and early reading ability and H0 is rejected